Implementation Of Dynamic Program In Determining The Optimum Path In The Distribution Of Pertamina Chemical & Agrochemical Lubricating Oil With Forward Recursive Equation PT.Pola Raya Jaya Sakti - Uswatun Hasanah Nasution; Fibri Rakhmawati (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
Pola Raya Jaya Sakti is a company engaged in the distribution of Pertamina Kimia & Agrochemical Lubricants. In its operations, this company is faced with the challenge of determining the optimum route in the lubricant oil distribution process in order to optimize production efficiency and reduce production costs. Based on research using a dynamic program with a Forward Recursive Equation, namely A → C → D → E → H → I → K → L → N → O → Q → R → S, where the sequence of locations is Jln. Sampali Road No 151 → Jln. Kesuma → Jln.Letda Sujono → Jln. Padang → Jln. Panglima Denai → Flyover Amplas → Tanjung Morawa → Lubuk Pakam → Tebing Tinggi → Ring Road Lima Puluh → Jln.Perintis Kemerdekaaan → Simpang Kawasan Ekonomi Khusus KEK Sei Mangkei → PT. Unilever Oleochemical Indonesia. The total distance is A+ C + E + H + I + L + N + O + Q + R = 0 + 8.5 km + 7.3 km + 4.4 km + 13 km + 70 km + 50 km + 16 km + 9.5 km+ 3 km = 181.7 km.